Judging Culpability in Dwyer’s Climate Change “Gaia Commission”: A Response to Dwyer - Valles, Sean (BioéthiqueOnline)

(untitled) (BioéthiqueOnline, 2015)
This commentary examines the concepts “recklessness, negligence and indifference” in James Dwyer’s short story, “The Gaia Commission: Climate Change and Moral Responsibility.”